Adaptability of breeds of rams and breed-types of range ewes to market lamb production in Kansas. - Bell, T.D.; Holland, L.A.; Gardner, A.W. (Kansas Agricultural Experiment Station, 2011)
Western ewes of the three predominant types (Texas ewes or finewools, Northwest Blackface Crossbreds, and Northwestern Whiteface Crossbreds) commonly found in Kansas were obtained as ewe lambs in the fall of 1951 and bred to Hampshire, Suffolk, Shropshire, and Southdown rams four seasons. A different set of rams has been used each year, and the ewes are being rotated so that no ewes are bred to the same breed of ram each year. Lamb-production and wool-production records are being obtained from the different types of ewes, and lamb-production figures are being obtained for the four sire groups.
Keywords: Sheep; Rams; Market lamb; Production